2011
DOI: 10.1002/asia.201000770
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline‐Intercalated Molybdenum Oxide Nanocomposites: Simultaneous Synthesis and their Enhanced Application for Supercapacitor

Abstract: A new and universal synthetic strategy to hybridize metal oxides and conduct polymer nanocomposites has been proposed in this work. The simultaneous reaction process, which includes the generation of metal oxide layers, the oxidation polymerization of monomers, and the in situ formation of polymer-metal oxides sandwich structure is successfully realized and results in the unique hybrid polyaniline (PANI)-intercalated molybdenum oxide nanocomposites. The peroxomolybdate proved to play a dual role as the precurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 43 publications
(70 reference statements)
2
26
0
Order By: Relevance
“…The polymer molecules are directed to grow along the large oriented tunnels of 3D hosts or interlayer space of the 2D hosts where the structurally organized frameworks are provided by the inorganic host. [ 6 ] But, main problem is that nanoparticles tend to self-aggregate due to their high surface energy which effectively reduces the contact area amongst the active materials, conductive materials, and electrolyte. So, it is very much essential to preserve the maximum available surface area of the active nanomaterials for their full utilizations.…”
mentioning
confidence: 99%
“…The polymer molecules are directed to grow along the large oriented tunnels of 3D hosts or interlayer space of the 2D hosts where the structurally organized frameworks are provided by the inorganic host. [ 6 ] But, main problem is that nanoparticles tend to self-aggregate due to their high surface energy which effectively reduces the contact area amongst the active materials, conductive materials, and electrolyte. So, it is very much essential to preserve the maximum available surface area of the active nanomaterials for their full utilizations.…”
mentioning
confidence: 99%
“…Tubular and sheetlike nanocomposites of MoO 3 with polyaniline intercalated between layers of the oxide were prepared [172]. After about 100 cycles the sheet-like material showed a larger specific capacitance of 200 F·g -1 vs 170 F·g -1 for the tubular one.…”
Section: Molybdenummentioning
confidence: 99%
“…[1][2][3][4] As one of the most promising types of energy storage devices, supercapacitors or ultracapacitors have drawn great interest owing to their distinguishable features such as higher power density and longer cyclic life than conventional batteries, higher en-ergy density than capacitor, high rate capacity, rapid charge discharge mechanism and environment friendliness. [5][6][7][8][9][10][11] Based on the charge storage mechanism, supercapacitors can be divided into two types involving, surface faradaic reactions (pseudocapacitors) and ion adsorption at the electrolyte/electrode interface (electric double layer capacitors, EDLCs). [12][13] Studies have shown that electrode materials are primarily responsible for overall supercapacitor performance.…”
Section: Introductionmentioning
confidence: 99%